El discurso de identidad y etnicidad en el ideal poscolonialista - de León González, Jorge Luis (2023)
The aim of this paper is to discuss regional identity and ethnicity and their representations, as seen from the collective imagination that people have used since the pre -Hispanic world until today to reconstitute themselves as revolutionary or as unique global subjects, in such a way that current behaviors are disrupted until symbols are created that represent the formation of local identity. This paper addresses the identity disc ourse used by different actors to position themselves in a given social context.